Comparison of Frontline Educational Workers experience Before and During Pandemic - Santos, Lara Mae F. Delos; Rueda, Rezza-Mira I. De; Sanchez, Ara Jane J.; Santos, John Vincent Llenada (EDUCATIO : Journal of Education, 2021)
The purpose of this research is to get insight into the first-hand experiences of educational frontline workers in the Philippines before to and during the Pandemic. The respondents were from Brgy. Rajal Centro Sta.Rosa Nueva Ecija and Gapan City Nueva Ecija. The participants in this study were selected frontline teachers who worked before and throughout the epidemic. This study focuses solely on the experiences of frontline employees prior to and during Covid-19. To determine if there is a substantial difference in frontline worker experience between covid-19 and before covid-19, or whether there is no significant difference. Taking into account each frontline worker's physical health, mental health, communication, and public perception, the findings of this study will be able to determine how significantly different the life experience has been and what recommendations can the frontline workers make in order to cope with the situation.